Seriatim : the Supreme Court before John Marshall - Gerber, Scott Douglas, 1961- (Book collections on Project MUSE., 1998)
"Seldom has American law seen a more towering figure than Chief Justice John Marshall. Indeed, Marshall is almost universally regarded as the 'father of the Supreme Court' and 'the jurist who started it all.' Yet even while acknowledging the indelible stamp Marshall put on the Supreme Court, it is possible--in fact necessary--to examine the pre-Marshall Court, and its justices, to gain a true understanding of the origins of American constitutionalism. The ten essays in this tightly edited volume were especially commissioned for the book, each by the leading authority on his or her particular subject. They examine such influential justices as John Jay, John Rutledge, William Cushing, James Wilson, John Blair, James Iredell, William Paterson, Samuel Chase, Oliver Ellsworth, and Bushrod Washington. The result is a fascinating window onto the origins of the most powerful court in the world, and on American constitutionalism itself."--JSTOR website (viewed March 7, 2017)